Organizational Culture and Digital Transformation: A Bibliometric Approach - Cruz-Cárdenas, Jorge (2022)
Organizational culture is a key to the success of business digital-transformation initiatives. The current study presents a bibliometric approach to the current knowledge of culture and digital transformation. For this purpose, 407 relevant documents were analyzed. The descriptive analysis indicated a panorama of great growth in the literature. An analysis of word co-occurrence in titles and abstracts was used to identify four areas of research interest: (1) training and learning among personnel, (2) cultural values that underpin the digital transformation, (3) environmental influences, and (4) technologies that enable digital transformation. Finally, little international collaboration between author networks was found.